(untitled) (Research, Society and Development, 2022)
Bacterial resistance is a global public health problem. The World Health Organization recently classified this issue as a priority for investment in the search for new antimicrobials. Given the scarcity of effective antimicrobials against resistant bacteria, the future focus of medical therapeutics and research is to look beyond traditional antimicrobials and seek alternatives that can regulate microbial virulence as well as growth inhibition. Recent trends in drug research from natural sources suggest that algae, in particular, hold promise for the discovery of new biochemically active substances. In view of this, the objective of this work is to describe the importance of the studies of antimicrobial compounds that are present in seaweed, since therapeutic innovations are necessary in order to be able to combat infections caused by resistant bacteria. The antimicrobial and antibiofilm activity of seaweed extracts against human bacterial pathogens has been reported by recent studies, indicating that seaweed extracts may represent therapeutic alternatives against resistant bacteria and the absence of effective drugs for the treatment of infections caused by superbacteria. Therefore, a bibliographic review of exploratory approach was carried out, presenting data and information exposed in articles, magazines, and scientific journals. Thirty-two articles ranging from the years 2018 to 2021, written in English and Portuguese languages, were selected. The data evaluated were the importance of the production of new antimicrobials, as well as effective results in the use of seaweed in the pharmaceutical industry.